Analisis Hubungan Antara Stunting dan Kapasitas Kognitif pada Anak Sekolah Dasar Usia 7-10 Tahun: Pendekatan Survei Analitik Desain Cross-Sectional - Silalahi, Micha; Munifah, Munifah; Hasan, Hasan (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The study was conducted to analyze the results of stunting of primary school children aged 7-10 years, the results of cognitive capacity of primary school children, and the relationship between stunting and children's cognitive capacity. The method used was analytical survey research with a cross-sectional approach design. The measuring instrument used was an intelligence test (IQ), namely CPM (Colored Progressive Matrics) interpreted by RAVEN, which was used to find the results of cognitive capacity and Weight Scales and Stature meters (measuring children's height). Sampling was determined through Anthropometric criteria of Child Nutritional Status Assessment with IMT/U index in the 5-18 years category through Waterlow criteria (< 95%). Data analysis techniques were used with Fisher's Exact Test, and the study's results found no significant relationship between stunting and cognitive capacity.